Enhanced Net K(+) Uptake Capacity of NaCl-Adapted Cells - Watad, Abd-Elrahem A. (1991)
Maintenance of intracellular K(+) concentrations that are not growth-limiting, in an environment of high Na(+), is characteristic of NaCl-adapted cells of the glycophyte, tobacco (Nicotiana tabacum/gossii). These cells exhibited a substantially greater uptake of (86)Rb(+) (i.e. an indicator of K(+)) relative to unadapted cells. Potassium uptake into NaCl-adapted cells was 1.5-fold greater than unadapted cells at 0 NaCl and 3.5-fold greater when cells were exposed to 160 millimolar NaCl. The difference in net K(+) uptake between unadapted and NaCl-adapted cells was due primarily to higher rates of entry rather than to reduced K(+) leakage. Presumably, enhanced K(+) uptake into adapted cells is a result of electrophoretic flux, and a component of uptake may be linked to vanadate-sensitive H(+) extrusion.